Respuesta :

Answer:  [tex]\dfrac{(x+9)^2}{225}-\dfrac{(y+7)^2}{49}=1[/tex]

Step-by-step explanation:

The equation for a horizontal ellipse is: [tex]\dfrac{(x-h)^2}{a^2}-\dfrac{(y-k)^2}{b^2}=1[/tex]  where

  • (h, k) is the center
  • a is x-radius
  • b is the y-radius

Given: major axis (diameter on x) is 30 --> x-radius (a) = 15  -->  a² = 225

           minor axis (diameter on y) is 14 --> y-radius (b) = 7   --> b² = 49

           center (h, k) is (-9, -7)

Input those values into the equation for a horizontal ellipse and simplify:

  [tex]\dfrac{(x-(-9))^2}{15^2}-\dfrac{(y-(-7))^2}{7^2}=1\\\\\\\large\boxed{\dfrac{(x+9)^2}{225}-\dfrac{(y+7)^2}{49}=1}[/tex]